Dranah Puṣhto - Pareshān Ḵẖaṭak, 1932- (Puṣhto Akaiḍaimī, Peṣhawar Yūnīwarsirī, 1978)
On the characteristics of the Pathans, with emphasis on Puṣhtūnwalī (code of laws or customs) for the settlement of their disputes.